2017
DOI: 10.1007/s12663-017-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

3-D Miniplates Versus Conventional Miniplates in Treatment of Mandible Fractures

Abstract: Aim To study whether the use of 3-D miniplate, when compared with conventional miniplate, gives better clinical outcomes with fewer complications in patients with fracture mandible. Materials and Methods A prospective study was conducted in the Department of Oral and Maxillofacial Surgery, Trauma Care Centre, on 40 patients. They were randomly divided into Group-I and Group-II with 20 patients in each group. In Group-I, 3-D miniplate was used and in Group-II, conventional miniplate was used. Parameters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
3
2
1
Order By: Relevance
“…The operating time of Suer K-miniplate was longer than the lateral border miniplate. This finding was consistent with studies done by Mishra et al [23] , Jain et al [28] and Singh et al [29] who found that the geometric miniplate system took more time in the angle region as compared with single miniplates. However there was no significant difference between the two groups and this is similar to Al-Moraissi et al results ( p = 0.141 between two groups).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The operating time of Suer K-miniplate was longer than the lateral border miniplate. This finding was consistent with studies done by Mishra et al [23] , Jain et al [28] and Singh et al [29] who found that the geometric miniplate system took more time in the angle region as compared with single miniplates. However there was no significant difference between the two groups and this is similar to Al-Moraissi et al results ( p = 0.141 between two groups).…”
Section: Discussionsupporting
confidence: 92%
“…[2] The postoperative mouth opening in both groups showed almost equal results at different time point and there wasn't statistical significance difference between the two groups. This may slightly differs from Mishra et al [23] results at 7th postoperative day findings as there was a significant difference between the geometric miniplates and the single miniplate. This may be due to their design of the geometric plate that needed more periosteal stripping than the Suer K-miniplate.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Even with good oral hygiene, long-term placement of plates is a factor that favors deterioration of tissue health because retention protocol requires placement until age 20. [ 21 ] The MH novel design of screws allows for multiple screw applications in a flapless technique with the ability to attach mini-plates above and away from the tissues without any contact, then secure that plate using small cover screws to the central holes of the MH screws [ Figure 5 ]. The clinician can use four to six screws as needed.…”
Section: Discussionmentioning
confidence: 99%